Pengaruh Online Customer Review terhadap Minat Menginap Konsumen pada Hotel di Kota Bandung - Aprilliana Dwi Handayani; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyse the influence of Online Customer Reviews on consumers’ intention to stay at four-star hotels in Bandung City. The development of information technology and digital platforms has made online customer reviews one of the primary sources of information for consumers when choosing accommodation. This research employs a quantitative approach using a survey method by distributing questionnaires to 170 respondents who have accessed hotel reviews online. The independent variables include review credibility, review valence, information quality, review quantity, and rating score, while the dependent variable is consumers’ intention to stay. Data were analysed using reliability testing and multiple linear regression analysis with the assistance of IBM SPSS Statistics software. The results indicate that the research instruments are reliable, with Cronbach’s Alpha values of 0.809 for the Online Customer Review variable and 0.771 for the intention to stay variable. Partially, review valence (? = 0.568; sig < 0.05), information quality (? = 0.260; sig < 0.05), and rating score (? = 0.587; sig < 0.05) have a positive and significant effect on consumers’ intention to stay. Review quantity (? = -0.417; sig < 0.05) has a significant but negative effect, while review credibility (sig > 0.05) does not have a significant effect. The most dominant factor influencing intention to stay is rating score, followed by review valence. These findings indicate that consumers rely more on aggregated ratings and overall sentiment rather than the credibility of individual reviewers. Therefore, managing ratings, improving review quality, and enhancing guest experience are crucial strategies to increase consumers’ intention to stay.